The battered woman called Eersterust : exploring thresholds through urban regeneration and re-adaptation of religious buildings - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.